Comparative Reproductive Biology of Deep-Sea Ophiuroids Inhabiting Polymetallic-Nodule Fields in the Clarion-Clipperton Fracture Zone - Laming, Sven R.; Christodoulou, Magdalini; Martinez Arbizu, Pedro; Hilário, Ana (Frontiers in Marine Science, 2021)
Deep-sea mining in the Pacific Clarion-Clipperton Fracture Zone (CCZ), a low-energy sedimentary habitat with polymetallic nodules, is expected to have considerable and long-lasting environmental impact. The CCZ hosts extraordinarily high species diversity across representatives from all Domains of Life. Data on species biology and ecology remain scarce, however. The current study describes the reproductive biology of Ophiosphalma glabrum (Ophiosphalmidae) and Ophiacantha cosmica (Ophiacanthidae), two ophiuroids frequently found in the CCZ. Specimens collected in Spring 2015 and 2019 in four contract areas were examined morphologically and histologically. Size-class frequencies (disc diameter and oocytes feret diameters), sex ratios, gametogenic status, putative reproductive mode, and a simple proxy for fecundity are presented. Habitat use differs in each. While O. glabrum is epibenthic, occurring as single individuals, O. cosmica often forms size-stratified groups living on stalked sponges, suggesting gregarious settlement or retention of offspring (though no brooding individuals were found). Further molecular analyses are needed to establish whether O. cosmica groups are familial. In O. glabrum, for which sample sizes were larger, sex ratios approximated a 1:1 ratio with no size-structuring. In both species, individuals were at various stages of gametogenic maturity, but no ripe females were identified. Based on this, O. glabrum is most probably gonochoric. Reproductive mode remains inconclusive for O. cosmica. Both species are presumptively lecithotrophic, with vitellogenic-oocyte feret diameters exceeding 250 μm. Oocyte feret diameters at times exceeded 400 μm in O. glabrum, indicating substantial yolk reserves. Estimates of instantaneous fecundity (vitellogenic specimens of O. glabrum only) were confounded by interindividual variability in gonad characteristics. The well-furnished lecithotrophic larvae of O. glabrum would be capable of dispersing even under food-impoverished conditions. The current study examines ophiuroid reproductive biology over multiple localities in the CCZ concurrently for the first time, at sites characterised by differing productivity regimes. The reproductive biology of each species is thus discussed with reference to past evolutionary (habitat stability), contemporary (food supply), and future environmental drivers (potential impacts of deep-sea mining).